2007
DOI: 10.1080/13557850601002155
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Comparison of Youth Risk Behaviors in Latino Secondary School Students Living in El Salvador and the USA

Abstract: In the context of the transnationalization of the Salvadoran population, with potential for increased influence of the USA in Salvadoran culture, these differences in risk behavior are important for targeting effective interventions for Latino adolescents in El Salvador and in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Findings from a cross-national study conducted by Dormitzer and colleagues (2004) among school-enrolled adolescents across Latin America suggest that rates of adolescent alcohol use (34%) in El Salvador are relatively low compared with other Latin and Central American nations, but that rates of tobacco (30%) and illicit drug use (8%) in El Salvador are at or above mean levels for nations across the Americas. School-based epidemiological studies of high school students in El Salvador suggest that Salvadoran adolescents in general are substantially less likely to report heavy episodic drinking (10%), cigarette use (34%), and the use of marijuana (5%), cocaine (3%), and inhalants (4%) compared with Hispanic adolescents in the United States (Springer, Kelder, Orpinas, & Baumler, 2007). However, given that the mean education level of Salvadoran youth is 7.5 years (UNDP, 2010) and that important substance use differences can be observed between school-enrolled and dropout youth (Townsend, Flisher, & King, 2007), it is likely that rates of substance use among Salvadoran youth in general may be substantially higher than those reported in the aforementioned studies.…”
Section: Youth Substance Use In El Salvadormentioning
confidence: 99%
“…Findings from a cross-national study conducted by Dormitzer and colleagues (2004) among school-enrolled adolescents across Latin America suggest that rates of adolescent alcohol use (34%) in El Salvador are relatively low compared with other Latin and Central American nations, but that rates of tobacco (30%) and illicit drug use (8%) in El Salvador are at or above mean levels for nations across the Americas. School-based epidemiological studies of high school students in El Salvador suggest that Salvadoran adolescents in general are substantially less likely to report heavy episodic drinking (10%), cigarette use (34%), and the use of marijuana (5%), cocaine (3%), and inhalants (4%) compared with Hispanic adolescents in the United States (Springer, Kelder, Orpinas, & Baumler, 2007). However, given that the mean education level of Salvadoran youth is 7.5 years (UNDP, 2010) and that important substance use differences can be observed between school-enrolled and dropout youth (Townsend, Flisher, & King, 2007), it is likely that rates of substance use among Salvadoran youth in general may be substantially higher than those reported in the aforementioned studies.…”
Section: Youth Substance Use In El Salvadormentioning
confidence: 99%
“…Rates of substance use differ by nativity status and foreign-born youth have been shown to have lower rates of use as compared to their native-born counterparts (Blake et al, 2001; Mullen Harris, 1999; Pena et al, 2008; Prado et al, 2009). However, most studies on substance use among immigrants have assessed differences by nativity (i.e., US vs. foreign-born nativity) or by generation (i.e., first, second, third) (Hussey et al, 2007; Mullen Harris, 1999; Prado et al, 2009; Springer et al, 2007). The vast majority of this work has found that foreign-born youth are at lower risk for substance use vis-à-vis their US born peers, but that risk increases linearly among second and third generation US-born youth (Hussey et al, 2007; Mullen Harris, 1999; Pena et al, 2008; Prado et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, published research on the validity and reliability of instruments purporting to measure supportive school relationships with Central American adolescent populations is limited. Because Central American adolescents share many of the same risk behaviors as U.S. adolescents, such as drug use [17] and aggressive behavior such as physical fighting [18,19], research on the protective effects of specific social contexts such as schools holds the potential to guide intervention efforts for reducing youth risk behavior initiation in Central American youth.…”
Section: Introductionmentioning
confidence: 99%